PL.32 Umbilical Artery Blood Analysis at the Time of Delivery: A Comparison Between Babies Born by Different Modes of Delivery. (26th April 2013) - Prior, T; Mullins, E; Bennett, P; Kumar, S
Abstract : Introduction: Umbilical cord arterial blood samples are taken routinely following delivery at many obstetric units in the UK. Whilst the pH of cord blood has been extensively investigated, other parameters have not. In this study we compared several parameters in cord blood between infants born by different modes of delivery. Methods: Umbilical artery cord blood samples taken immediately following delivery from 469 infants were analysed to compare pH, base deficit, lactate, glucose, p02 and pCO2. These values were then compared using one-way ANOVA testing to determine if significant differences existed between the different mode of delivery groups. Results: Significant differences in the mean base excess, lactate, glucose and pO2 levels were observed between the different mode of delivery groups. Infants delivered by emergency Caesarean section for fetal compromise had the lowest pO2 and lowest glucose level of all mode of delivery groups, as well as the smallest base deficit and lowest lactate levels. No significant difference was observed in pH levels between the different mode of delivery groups. Conclusions: Umbilical artery pH at delivery is one mechanism used to evaluate the fetal condition at the time of delivery. We found no variation in umbilical artery pH between the different mode of delivery groups. This may have been due to resuscitative measures following the diagnosis of fetal compromise. However, despite this, significant differences in p02 and glucose levels remained. Further investigation of these parameters may allow better fetal assessment both intra-partum, and at the time of delivery.